2021
DOI: 10.1093/rap/rkab013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fatigue in hip and/or knee osteoarthritis: a systematic review and best evidence synthesis

Abstract: Objective To systematically identify and evaluate factors related to fatigue in individuals with hip and/or knee osteoarthritis (OA). Methods A systematic literature search was conducted using AMED, CINAHL, MEDLINE, ProQuest and Web of Science Core Collections databases. Inclusion criteria comprised cross-sectional, case-control or longitudinal studies on patients with a diagnosis of hip and/or knee OA that included self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…The NHLBI tool is a widely used assessment tool for evaluating qualities of epidemiological studies. The NHLBI tool allowed for assessment of methodological flaws, such as sampling, adjustment for confounders, study power and other relevant factors for the study [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The NHLBI tool is a widely used assessment tool for evaluating qualities of epidemiological studies. The NHLBI tool allowed for assessment of methodological flaws, such as sampling, adjustment for confounders, study power and other relevant factors for the study [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The worsening of pain in the COVID-19 period in older adults with osteoarthritis is suggested by the results of the study done by Román Belmonte et al [ 64 ]. Clinically, older adults with osteoarthritis report the presence of pain and fatigue as significant limiting factors in the domain of physical activity [ 65 , 66 ]. Studies suggest an association of iron deficiency anemia with reduced muscle mass and strength, reduced motor ability and the presence of disability.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms of knee OA include movement disorders due to pain, muscle weakness, and range of motion (ROM) limitations, as well as physical activity restriction, and represent a major problem (Christiansen et al., 2018; Muraki et al., 2015). Previous studies have reported that decreased physical activity in patients with knee OA not only promotes obesity and poor functional ability but also has adverse effects, such as fatigue, depression, and kinesiophobia (Aykut Selçuk & Karakoyun, 2020; Fawole et al., 2021). Therefore, improving low physical activity is important for treating knee OA.…”
Section: Introductionmentioning
confidence: 99%